Accoounting : A Comparative Analysis Between the Era of Rasulullah and Khulafaur Rasyidin and 6th Century Europe (Value : Jurnal Manajemen dan Akuntansi, 2025)
This study examines the comparison of accounting practices during the era of Prophet Muhammad SAW and the Khulafaur Rashidin with accounting practices in 6th century Europe. This period is significant for exploring the development of financial recording systems in two distinct cultural and religious contexts. The study aims to analyze the similarities and differences in principles, techniques, and purposes of accounting in both regions and to understand the influence of social, political, and religious factors on the evolution of accounting practices. A qualitative approach was adopted using literature review methods. Data were gathered from primary sources such as historical documents, trade records, and religious literature, as well as secondary sources from modern academic research. The research reveals that accounting practices during the era of Prophet Muhammad SAW and the Khulafaur Rashidin were deeply rooted in religious values such as honesty, justice, and accountability, integrated into financial records. Meanwhile, accounting practices in 6th century Europe focused more on administrative aspects and served the needs of feudalism, heavily influenced by church structures. Fundamental differences were also found in the forms of documentation and the purposes of financial reports. Accounting practices in both regions highlight the close connection between accounting systems and socio-cultural contexts. This study emphasizes the importance of understanding the history of accounting as a foundation for the development of modern accounting systems.
Keywords: Accounting; A Comparative Analysis; Rasulullah and Khulafaurrosyidin; 6th Century Europe